2019
DOI: 10.1101/649822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

7 Tesla MRI of the ex vivo human brain at 100 micron resolution

Abstract: 1We present an ultra-high resolution MRI dataset of an ex vivo human brain 2 2 specimen. The brain specimen was donated by a 58-year-old woman who 2 3 had no history of neurological disease and died of non-neurological causes. 4After fixation in 10% formalin, the specimen was imaged on a 7 Tesla MRI 2 5 scanner at 100 µm isotropic resolution using a custom-built 31-channel 2 6 receive array coil. Single-echo multi-flip Fast Low-Angle SHot (FLASH) data 2 7 were acquired over 100 hours of scan time (25 hours per… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 29 publications
0
74
0
1
Order By: Relevance
“…This was the case for most patients, and fibers predominantly connected to the sensorimotor strip (M1, SMA or pre-SMA). (Ewert et al, 2018), an axial plane of the 7T MRI ex vivo human brain template (Edlow et al, 2019) is shown at z = -10 mm. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted February 27, 2020. .…”
Section: Resultsmentioning
confidence: 99%
“…This was the case for most patients, and fibers predominantly connected to the sensorimotor strip (M1, SMA or pre-SMA). (Ewert et al, 2018), an axial plane of the 7T MRI ex vivo human brain template (Edlow et al, 2019) is shown at z = -10 mm. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted February 27, 2020. .…”
Section: Resultsmentioning
confidence: 99%
“…A 3D MRI dataset of an autopsy brain can be generated using a clinical 3-T MRI scanner overnight -this also makes it much more feasible to generate 3D datasets from many individual brains. A recent report described creation of a 3D 100micron isotropic resolution MRI dataset using a 100-hr scan (∼4 days) on a 7-T MRI system -the technically challenging and long acquisition may limit the ability to generate a library of multiple individual brains using such a protocol (Edlow et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…All ex vivo datasets were acquired on a clinical 3-T scanner using a modified SPACE sequence. Potential improvement of ex vivo structure assignments may result from a combined approach utilizing different contrasts such as diffusion, susceptibility or higher field strengths (7-T) (Edlow et al, 2019). Ultra-high field scanners can be prone to increased geometric distortion and signal loss at the skull base but have potential to improve resolution for in vivo acquisitions (Zeineh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the method is expected to run faster for large MRI volumes, or for the detection of larger lesions. Ex vivo imaging of human brain, which has attracted researchers to explore microstructural neuroanatomy, can produce brain images with (0.1mm) 3 isometric voxel resolution [27]. As the resolution increases, the ROI volume size increases proportionally, necessitating the reduction in computational complexity of the algorithms for processing very large MRI volumes to automatically detect lesions.…”
Section: Discussionmentioning
confidence: 99%